Analysis of International Marketing Development Strategies for Ornamental Coral to Increase Sales Turnover of PT. Panorama Alam Tropika Jakarta - Kasmi, Mauli (International Journal of Education, Vocational and Social Science, 2023)
Panorama Alam Tropika is an agribusiness company that exports ornamental coral. The purpose of this research is to determine the international marketing strategy at PT. Panorama, to identify the obstacles faced by PT. Panorama Alam Tropika in increasing sales turnover, and also to determine the efforts made by PT. Panorama Alam Tropika in increasing sales turnover. Descriptive research can provide an overview of a problem, phenomenon, fact, event, and reality in a broad and deep way so that a new understanding is obtained, then the qualitative method will be more appropriate. For the development of international marketing strategies, the STP (Segmenting, Targeting, Positioning) model and 4P Strategy (Production, Promotion, Place, and Price) are used. This marketing mix is used for both the domestic and international markets. PT. Panorama uses a 4P marketing strategy that is good enough except for promotion where the company still focuses on advertising exported ornamental coral products only. Then the price of PT. Panorama's products is adjusted to the cost of raw materials needed, labor, promotion costs, product distribution costs, estimated profits that can be taken from the economic conditions of the market. The price of products for the international market is adjusted to the exchange rate of the destination country. Furthermore, PT. Panorama determines the location by finding a crowded location, a location with easy access, and the company also determines the business location by calculating in a representative location.